2021
DOI: 10.1038/s41598-021-93509-w
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the landscape of chromatin dynamics during naïve CD4+ T-cell activation

Abstract: T-cell activation induces context-specific gene expression programs that promote energy generation and biosynthesis, progression through the cell cycle and ultimately cell differentiation. The aim of this study was to apply the omni ATAC-seq method to characterize the landscape of chromatin changes induced by T-cell activation in mature naïve CD4+ T-cells. Using a well-established ex vivo protocol of canonical T-cell receptor signaling, we generated genome-wide chromatin maps of naïve T-cells from pediatric do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Meanwhile, increasing evidence suggests that enhancer–promoter interactions are also crucial for gene expression regulation [ 31 ]. Studies have shown that the majority of chromatin accessibility found during induction of T cell activation by omni ATAC-seq were located in intergenic enhancer regions [ 32 ]. A large fraction of chromatin accessibility in our study was located in intergenic regions, further suggesting that enhancers may interact with TFs and promoters to regulate gene expression during yak adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, increasing evidence suggests that enhancer–promoter interactions are also crucial for gene expression regulation [ 31 ]. Studies have shown that the majority of chromatin accessibility found during induction of T cell activation by omni ATAC-seq were located in intergenic enhancer regions [ 32 ]. A large fraction of chromatin accessibility in our study was located in intergenic regions, further suggesting that enhancers may interact with TFs and promoters to regulate gene expression during yak adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the likelihood that changes in DNA methylation corresponded to changes in chromatin accessibility, we compared these activation‐associated DMPs (commonly activated, NA‐specific and FA‐specific) with a publicly available ATAC‐seq dataset for nCD4T cells at quiescence and following activation using the same approach (72 h with anti‐CD3/CD28) 34 . We identified enrichment for ATAC‐peaks in commonly activated DMPs (33% relative to 21% for all EPIC probes; [ Χ 2 (3, N = 11,584) = 82.7, p value <.01)] (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Assay for Transposable Accessible Chromatin (ATAC)‐seq fastq files for quiescent and activated T cells were downloaded from GEO (GSE157174) 34 . ATAC‐seq reads were aligned to human genome assembly hg19 using bwa 35 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated and differentiated T-helper cells possessed differentially expressed accessible chromatin region at enhancers and introns compared to quiescent counterparts ( 84 ). This indicates a rapid remodelling of the genome under stimulation.…”
Section: Immune Loci Regulation By the Cohesin Complexmentioning
confidence: 99%